The Strategy of the Purwakarta Regency Government in Absorbing Community Aspirations through the Gempungan Program in Batu Tumpang Village, Tegalwaru District, Purwakarta Regency - Luthfi Faisal Natsir (Penerbit Hellow Pustaka, 2025)
This thesis is the result of research on Purwakarta County Government Strategy Absorb Aspirations In Society Through Gempungan Program at Stones Village Overlapping Sub District Tegalwaru Purwakarta 2012. Gempungan Program is one of the tips Regent Purwakarta with a meeting between the leaders of the community to discuss solve the problems that exist at the village level program / activity is in the form of direct services Gempungan of Purwakarta district government to the people, especially the activity is done once a week rotating every village , which include the administrative issues of population, health, and other problems experienced by the community and are ready to interact to solve problems. The method I used is descriptive method with qualitative approach with data collection techniques through library research and field study consisting of observations and interviews. The parameters contained in this thesis, namely planning, and the purpose of which to achieve the success of the District Government Strategy Purwakarta Absorb Aspirations In Society Through Gempungan Program at Stones Village District Overlapping Tegalwaru 2012. From the results of research and discussion can be concluded that in order to achieve the success of the strategy seen from the plan, and purpose. It can be seen from the plan by each implementing organization before conducting Gempungan program that aims to absorb the aspirations of the people at the village level by providing free services done in one full day. Thus, the authors provide advice to the Government of the District of Purwakarta that might be useful for improvement in development strategies in the District Government Purwakarta Absorb Gempungan Aspirations Program in Community Through Overlapping sub Village Stones Tegalwaru Purwakarta district in 2012 ie at the stage of implementation of these activities should be done for two day, on the first day of free services and activities on the second day of a meeting between the Regent Purwakarta with communities to absorb the people's aspirations.